2022
DOI: 10.3389/fnins.2022.933520
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Vestibular Disorders Presenting With Acute Continuous Vertigo

Abstract: ObjectiveTo explore the composition of vestibular disorders presenting with the acute vestibular syndrome (AVS).MethodsWe performed a case analysis of 209 AVS patients between January 2016 and December 2020. These patients were grouped into different disorder categories according to the relevant diagnostic criteria.ResultsWe classified the 209 patients into 14 disorder categories, including 110 cases of vestibular neuritis, 30 of idiopathic sudden sensorineural hearing loss with vertigo, 17 of the first attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Headache (91.7%) and visual disturbances (58%) are the most common symptoms, according to the literature [17,18] . According to Danilowicz, 75-100% of patients with visual perspective changes, 54.2% of patients with anterior pituitary dysfunction, and the following syndromes led to panhypopituitarism: adrenocortical adenoma, adrenocortical adenoma, adrenocortical ade decreased libido, cold intolerance, amenorrhea, polyuria, and polydipsia made up 50% of the symptoms [19] . Diabetes insipidus (DI) almost accounts for nearly 50% of PA compared to 10% of pituitary adenoma, indicating that DI aids in diagnosing PA [20] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Headache (91.7%) and visual disturbances (58%) are the most common symptoms, according to the literature [17,18] . According to Danilowicz, 75-100% of patients with visual perspective changes, 54.2% of patients with anterior pituitary dysfunction, and the following syndromes led to panhypopituitarism: adrenocortical adenoma, adrenocortical adenoma, adrenocortical ade decreased libido, cold intolerance, amenorrhea, polyuria, and polydipsia made up 50% of the symptoms [19] . Diabetes insipidus (DI) almost accounts for nearly 50% of PA compared to 10% of pituitary adenoma, indicating that DI aids in diagnosing PA [20] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“… 1 , 4 , 5 , 6 , 7 , 8 However, the subjective nature of vertigo and the heterogeneity of study populations causes variability in the reported results. 6 , 7 , 8 , 9 Moreover, few studies have explored the differences in vestibular function between SSNHL and vertigo, which can be considered labyrinthitis and VN, 5 , 10 and little is known about the differences and characteristics of the vestibulo‐ocular reflex (VOR) between these two diseases.…”
Section: Introductionmentioning
confidence: 99%